1980
DOI: 10.1099/00221287-120-2-301
|View full text |Cite
|
Sign up to set email alerts
|

The Deposition of Streptococcus sanguis NCTC 7868 from a Flowing Suspension

Abstract: Measurements were made of the rates at which continuously cultured Streptococcus sanguis NCTC 7868 cells accumulated on the inside surfaces of narrow glass capillaries from suspensions of the bacteria flowing down the capillaries at different velocities. Initially, the rate of accumulation of bacteria on the clean walls of the capillary was rapid. The deposition rate decreased with time, however, resulting in a saturation coverage of the glass surface which was considerably less than a monolayer. Multilayer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Reduced adhesion or sticking efficiency at high shear rates has been reported before (Duddridge et al, 1982;Lau and Liu, 1993;Powel and Slater, 1983;Rutter and Leech, 1980). Rutter and Leech (1980) suggested that it can be explained by a polymer bridging mechanism for adhesion.…”
Section: P Putida Adhesion Studiesmentioning
confidence: 87%
See 2 more Smart Citations
“…Reduced adhesion or sticking efficiency at high shear rates has been reported before (Duddridge et al, 1982;Lau and Liu, 1993;Powel and Slater, 1983;Rutter and Leech, 1980). Rutter and Leech (1980) suggested that it can be explained by a polymer bridging mechanism for adhesion.…”
Section: P Putida Adhesion Studiesmentioning
confidence: 87%
“…Reduced adhesion or sticking efficiency at high shear rates has been reported before (Duddridge et al, 1982;Lau and Liu, 1993;Powel and Slater, 1983;Rutter and Leech, 1980). Rutter and Leech (1980) suggested that it can be explained by a polymer bridging mechanism for adhesion. After a relatively weak physical adsorption, during which lateral displacement of the cells over a homogenous surface does not in- fluence the interactions, the cells are anchored to the carrier surface by bridges or extracellular polymers.…”
Section: P Putida Adhesion Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Cell multiplication due to growth should also be eliminated or minimized. Techniques using small glass capillaries have been developed by a number of authors (19,22). Generally, the deposition rate of cells to the glass walls of the capillary is much less than the collision rate.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…This could result in an increase in adhesion to the surface, as with polystyrene latex beads (Rutter and leach 1980). However, this is not always the case with bacteria as in this study, and with Streptococcus sanguis NCTC 7868, adhering to the walls of glass capillaries (Rutter and Leech 1980). The effect of conditioning of a surface on the adherence of bacteria is difficult to determine.…”
Section: ------------------------------------------------------------mentioning
confidence: 62%